The Security of Arithmetic Compression Based Text Steganography Method - Reihane Saniei; Karim Faez (Institute of Advanced Engineering and Science, 2013)
Security of a modern design of steganography on lossless compression isstudied in this paper. Investigation of a set of methods presented hereindicates that there are various approaches to establish a hidden and saferelationship with the minimum cost for text files. Although, steganography of information in text is one of the most difficult areas of steganography, many efforts were made in this regard. With regard to the spread of this category and existence of wide volume of approaches, this paper deals with comparison and evaluation of steganography security by a statisticalcompression method called arithmetic coding and other methods of textsteganography. Moreover, this method is available for audio-visual and video files. In addition, stego key was placed in a format that it would not arouse any suspicions. It is notable that this new method of steganography or rewriting and syntactic and semantic review does not reveal the secret message and results in 82.88% improvement in security.DOI:http://dx.doi.org/10.11591/ijece.v3i6.4068